A practical guide to Red Hat Linux : Fedora Core and Red Hat Enterprise Linux - Sobell, Mark G. (Upper Saddle River, NJ : Prentice Hall, 2007)
This edition covering Fedora Core 5 and Red Hat Enterprise Linux version 4 covers their upgraded security, shell script-writing, and other features. With some overlap with the author's previous books on Linux and UNIX, chapters include practical examples, tip and caution boxes, optional advanced sections, and review exercises. Appendices offer further details on regular expressions, the meaning of "free" software, the last Linux (2.6) kernel, plus troubleshooting resources and a glossary. The DVD-ROM contains the full Fedora Core 5. Limited time free access to an online edition is available. Programming experience is not required but programmers are among the intended audience along with students, home users, and system administrators.
Linux -- Installing Fedora and Red Hat Enterprise Linux -- Installation Overview -- Getting Started with Fedora and Red Hat Enterprise Linux -- Introduction to Fedora and Red Hat Enterprise Linux -- The Linux Utilities -- The Linux Filesystem -- The Shell -- Digging into Fedora and Red Hat Enterprise Linux -- Linux GUIs: X, GNOME, and KDE -- The Bourne Again Shell -- Networking and the Internet -- System Administration -- System Administration: Core Concepts -- Files, Directories, and Filesystems -- Downloading and Installing Software -- Printing with CUPS -- Rebuilding the Linux Kernel -- Administration Tasks -- Configuring a LAN -- Using Clients and Setting Up Servers -- Transferring Files Across a Network -- sendmail: Setting Up Mail Clients, Servers, and More -- NIS and LDAP -- NFS: Sharing Filesystems -- Samba: Integrating Linux and Windows -- DNS/BIND: Tracking Domain Names and Addresses -- iptables: Setting Up a Firewall -- Apache (httpd): Setting Up a Web Server -- Programming -- Programming Tools -- Programming the Bourne Again Shell --
Includes index.
1
Keywords: Linux; CIT; Operating systems (Computers)